PTU-049 Management of dysphagia in patients with oesophageal cancer. (22nd June 2015) - Chadwick, G; Groene, O; Hardwick, R; Crosby, T; Riley, S; Cromwell, D
Abstract : Introduction: The commonest symptom associated with oesophageal cancer is dysphagia, this is frequently managed with an oesophageal stent. A randomised trial 1 suggested that for patients with a life expectancy of >3 months, brachytherapy may provide better symptom relief with fewer complications. But uptake appears to be low in the UK. In 2010, only 54% of Cancer Networks reported having access to brachytherapy. 2 This study investigated the use of these therapeutic options in England and Wales. Method: The study used data from the National Oesophago-Gastric Cancer Audit, limited to patients diagnosed with oesophageal cancer between 1 st April 2011 and 31 st March 2013 in England and Wales, where treatment intent was palliative and patients received either brachytherapy or endoscopic stenting. We compared patient characteristics, complication rates and survival across the two groups. Results: Overall 9, 252 patients were included in the study. Of these 2, 333 had an oesophageal stent placed, 49 had brachytherapy and 4 had both. Patient characteristics varied significantly between the two groups (Table 1 ). The most frequent choice of stent was covered metal (83.2%), with the majority of stents were placed under combined fluoroscopic and endoscopic control (38.2%) or endoscopic control alone (31.9%). 98.3% of stents were successfully inserted. Complication rates associated with both brachytherapy and stenting were under 2%, with no statistically significant difference. Post-intervention 90-day mortality after brachytherapy was 8.2% (95% CI 0.02–16.1%) suggesting appropriate use. But after stent insertion median survival 95 days (IQR: 42–189). This suggests some patients may have been suitable for brachytherapy. Conclusion: Half of patients who had a stent inserted survived more than 3 months, these patients may have achieved better symptom control with fewer complications with brachytherapy instead. 1 Only 9 NHS trusts reported using brachytherapy, suggesting it is currently underutilised. Disclosure of interest: None Declared. References: Homs MYV, Steyerberg EW, Eijkenboom WMH, et al . Single-dose brachytherapy versus metal stent placement for the palliation of dysphagia from oesophageal cancer: multicentre randomised trial. Lancet 2004;364:1497–504 Groene O, Chadwick G, Riley S, et al . Re-organisation of oesophago-gastric cancer services in England and Wales: a follow-up assessment of progress and remaining challenges. BMC Research Notes 2014;7:24